Repurposing of oxazolone chemistry: gaining access to functionalized graphene nanosheets in a top-down approach from graphite. Issue 12 (8th September 2015) - Neri, Giulia; Scala, Angela; Fazio, Enza; Mineo, Placido G.; Rescifina, Antonio; Piperno, Anna; Grassi, Giovanni
Abstract : Solvent-free 1, 3-dipolar cycloaddition reactions of graphite flakes and mesoionic oxazolones lead to the direct functionalization and delamination of graphite flakes into few layers of graphene nanosheets. Abstract : Solvent-free 1, 3-dipolar cycloaddition (1, 3-DC) reactions between graphite flakes and mesoionic oxazolones were carried out by heating the resulting solid mixture at mild temperatures (70–120 °C). The direct functionalization and delamination of graphite flakes into few layers of graphene nanosheets was confirmed by micro-Raman and X-ray photoelectron spectroscopies, scanning transmission electron microscopy and thermogravimetric analysis. The 1, 3-DC reactions of mesoionic dipoles have been investigated with density functional theory to model graphene, exploring three different pathways: center, corner and edge. These theoretical calculations highlighted that the 1, 3-DC reaction can proceed both through a concerted mechanism competing with a stepwise one involving a zwitterionic intermediate. The irreversible decarboxylation inherent in the last step justifies the high degree of functionalization experimentally observed, representing the driving force of the process.